Pengaruh Metode Karya Wisata Terhadap Kemampuan Literasi Anak Usia 5 - 6 Tahun - Darmina Ardianur S Putri; Herlina Hasan; Gappar (Ihya Ulum: Early Childhood Education Journal, 2023)
This experimental study aims to (a) determine the application of the learning method of tourism in the Kindergarten Negeri 001 Timur, Bulungan Regency, North Kalimantan Province, (b) describe children's literacy skills before and after learning with the tourism method in the Kindergarten, and (c) identify differences between the experimental group (tourism method) and the control group in improving children's literacy skills in the Kindergarten. The results showed that the learning method of field trips in the kindergarten was effective in improving children's literacy skills. Before learning, children's literacy skills in the control class were in the low category, while in the experimental class were also in the low category. However, after learning, children's literacy skills in the control class increased to the medium category, while in the experimental class it increased to the high category. There is a significant difference in the effect of the field trip method on children's literacy skills in the kindergarten, which is indicated by an increase in the average literacy score from 5.89 to 8.67 after treatment. This is also supported by the results of hypothesis testing with the value of t count> t table at the 5% significance level.